2 years of calorie restriction and cardiometabolic risk (CALERIE): exploratory outcomes of a multicentre, phase 2, randomised controlled trial. Issue 9 (September 2019) - Kraus, William E; Bhapkar, Manjushri; Huffman, Kim M; Pieper, Carl F; Krupa Das, Sai; Redman, Leanne M; Villareal, Dennis T; Rochon, James; Roberts, Susan B; Ravussin, Eric; Holloszy, John O; Fontana, Luigi; et al.
Summary: Background: For several cardiometabolic risk factors, values considered within normal range are associated with an increased risk of cardiovascular morbidity and mortality. We aimed to investigate the short-term and long-term effects of calorie restriction with adequate nutrition on these risk factors in healthy, lean, or slightly overweight young and middle-aged individuals. Methods: CALERIE was a phase 2, multicentre, randomised controlled trial in young and middle-aged (21–50 years), healthy non-obese (BMI 22·0–27·9 kg/m 2 ) men and women done in three clinical centres in the USA. Participants were randomly assigned (2:1) to a 25% calorie restriction diet or an ad libitum control diet. Exploratory cardiometabolic risk factor responses to a prescribed 25% calorie restriction diet for 2 years were evaluated (systolic, diastolic, and mean blood pressure; plasma lipids; high-sensitivity C-reactive protein; metabolic syndrome score; and glucose homoeostasis measures of fasting insulin, glucose, insulin resistance, and 2-h glucose, area-under-the curve for glucose, and insulin from an oral glucose tolerance test) analysed in the intention-to-treat population. This study is registered withClinicalTrials.gov, numberNCT00427193 . Findings: From May 8, 2007, to Feb 26, 2010, of 238 participants that were assessed, 218 were randomly assigned to and started a 25% calorie restriction diet (n=143, 66%) or an ad libitum control diet (n=75, 34%). Individuals in the calorie restriction group achieved a mean reduction in calorie intake of 11·9% (SE 0·7; from 2467 kcal to 2170 kcal) versus 0·8% (1·0) in the control group, and a sustained mean weight reduction of 7·5 kg (SE 0·4) versus an increase of 0·1 kg (0·5) in the control group, of which 71% (mean change in fat mass 5·3 kg [SE 0·3] divided by mean change in weight 7·5 kg [0·4]) was fat mass loss. Calorie restriction caused a persistent and significant reduction from baseline to 2 years of all measured conventional cardiometabolic risk factors, including change scores for LDL-cholesterol (p<0·0001), total cholesterol to HDL-cholesterol ratio (p<0·0001), and systolic (p<0·0011) and diastolic (p<0·0001) blood pressure. In addition, calorie restriction resulted in a significant improvement at 2 years in C-reactive protein (p=0·012), insulin sensitivity index (p<0·0001), and metabolic syndrome score (p<0·0001) relative to control. A sensitivity analysis revealed the responses to be robust after controlling for relative weight loss changes. Interpretation: 2 years of moderate calorie restriction significantly reduced multiple cardiometabolic risk factors in young, non-obese adults. These findings suggest the potential for a substantial advantage for cardiovascular health of practicing moderate calorie restriction in young and middle-aged healthy individuals, and they offer promise for pronounced long-term population health benefits. Funding: National Institute on Aging and National Institute of Diabetes and Digestive and Kidney Diseases, National Institutes of Health.